ATPMN: Accurate positions and flux densities at 5 and 8GHz for 8385 sources from the PMN survey - McConnell, D.; Sadler, E.; Murphy, T.; Ekers, Ronald (Oxford University Press, 2012)
We present a source catalogue of 9,040 radio sources resulting from high-resolution observations of 8,385PMN sources with the Australia Telescope Compact Array. The catalogue lists flux density and structural measurements at 4.8 and 8.6 GHz, derived from observations of all PMN sources in the declination range −87° < δ < −38.°5 (exclusive of galactic latitudes |b| < 2°) with flux density S4850 ≥ 70 mJy (50 mJy south of δ = −73°). We assess the quality of the data, which was gathered in 1992–1994, describe the population of catalogued sources, and compare it to samples from complementary catalogues. In particular we find 127 radio sources with probable association with γ-ray sources observed by the orbiting Fermi Large Area Telescope.